Pneumocystis carinii infection with severe pneumomediastinum and lymph node involvement in a Whippet mixed-breed dog. (September 2017) - Weissenbacher-Lang, Christiane; Fuchs-Baumgartinger, Andrea; Klang, Andrea; Kneissl, Sibylle; Pirker, Armin; Shibly, Sarina; von Ritgen, Stephanie; Weissenböck, Herbert; Künzel, Frank
A 3.5-y-old Whippet mixed-breed dog was presented with a history of respiratory distress, exercise intolerance, and generalized demodicosis. Hematologic alterations included marked leukocytosis and neutrophilia. Radiographic examination showed a diffuse interstitial and mild peripheral alveolar lung pattern and pneumomediastinum. Because the cytologic examination of the bronchoalveolar aspirate was not diagnostic and a persistent perforation of the upper respiratory tract could not be ruled out, the dog was submitted to thoracoscopy, and subsequently the left cranial lung lobe as well as mediastinal and sternal lymph nodes were resected. Pulmonary pneumocystosis with spread to the thoracic lymph nodes was suspected after histologic investigation of lung and lymph nodes, which was confirmed by in situ hybridization, PCR, and subsequent Sanger sequencing. We document a rare, simultaneous occurrence of severe pulmonary and thoracic lymph node pneumocystosis with spontaneous pneumomediastinum in a dog. Definitive diagnosis was achieved through the use of Grocott methenamine silver staining, in situ hybridization, and PCR.